Structural phase transitions in YPtGe2 and GdPtGe2. Issue 17 (17th April 2018) - Janka, Oliver; Hoffmann, Rolf-Dieter; Heying, Birgit; Pöttgen, Rainer
Abstract : The germanides YPtGe2 and GdPtGe2 were synthesized from REGe2 precursor compounds and platinum by arc-melting and their structures were studied on the basis of temperature-dependent single crystal X-ray diffraction data. Abstract : The germanides YPtGe2 and GdPtGe2 were synthesized from REGe2 precursor compounds and platinum by arc-melting and their structures were studied on the basis of temperature-dependent single crystal X-ray diffraction data. At room temperature both germanides adopt the orthorhombic YIrGe2 type structure, space group Immm, with enhanced U 11 displacement parameters for the Ge1 atoms. Below 174 and 145 K, respectively, satellite reflections emerge in the diffraction patterns, giving rise to modulations. The low-temperature structures were refined in the superspace group Pnnn (1/2, 1/2, γ ) qq 0 (48.1.11.3). The structural phase transition is also evident in the magnetic susceptibility, specific heat and resistivity data. The high- and low-temperature modifications are discussed on the basis of a group–subgroup scheme.